Briquettes from Tobacco Stems as the New Alternative Energy - Okta Prima Indahsari (Research Center for Chemistry - LIPI, 2017)
Tobacco briquettes is the new alternative energy developed in PTPerkebunan Nusantara X (PTPN X). The tobacco briquettes research isimportant for PTPN X because of three reasons: high availability of theraw material, it can be used as substitution for coal briquettes, andexpected for industrial scale. Currently, many researches have beenconducted for biomass-briquettes but only few who used tobacco. PTPN Xhave been cultivated tobacco only for its leaves which latter used for cigarand the rests were thrown as waste. By conducting the tobacco briquettesresearch, many forms of utilization are expected. For short term, the aimof this research is generating a diversification of added value - producfrom tobacco. For middle term, PTPN X is expected to be the role modelfor the tobacco growers. For long term, PTPN Xl’s goal is to decreasecoal briquettes usage and break the negative stigma of tobacco.Briquetting process was conducted in Physical Laboratory of TobaccoResearch of Jember and the observation located in Tobacco ProcessingBarn of Ajong Gayasan PTPN X. Analysis of proximate test showed thatthe moisture content of tobacco briquettes with cassava starch as adhesivewas 8.00 to 8.97%, the volatile matter was 49.60 to 41.13%, the ashcontent was 9.93 to 7.89%, the fixed carbon was 32.47% to 42.01%, thesulphur content was 1.02 to 0.49%, the bulk density was from 0.35% to0.41%, the calorific value was from 4,285 to 4,586 cal/gr, and flammableduration was from 592 to 697 minutes. The briquetting process did notaffect the taste of leaves as cigar material.